Is adding maternal vaccination to prevent whooping cough cost-effective in Australia?. Issue 9 (2nd September 2018) - Van Bellinghen, Laure-Anne; Dimitroff, Alex; Haberl, Michael; Li, Xiao; Manton, Andrew; Moeremans, Karen; Demarteau, Nadia
ABSTRACT: Pertussis or whooping cough, a highly infectious respiratory infection, causes significant morbidity and mortality in infants. In adolescents and adults, pertussis presents with atypical symptoms often resulting in under-diagnosis and under-reporting, increasing the risk of transmission to more vulnerable groups. Maternal vaccination against pertussis protects mothers and newborns. This evaluation assessed the cost-effectiveness of adding maternal dTpa (reduced antigen diphtheria, Tetanus, acellular pertussis) vaccination to the 2016 nationally-funded pertussis program (DTPa [Diphtheria, Tetanus, acellular Pertussis] at 2, 4, 6, 18 months, 4 years and dTpa at 12–13 years) in Australia. A static cross-sectional population model was developed using a one-year period at steady-state. The model considered the total Australian population, stratified by age. Vaccine effectiveness against pertussis infection was assumed to be 92% in mothers and 91% in newborns, based on observational and case-control studies. The model included conservative assumptions around unreported cases. With 70% coverage, adding maternal vaccination to the existing pertussis program would prevent 8, 847 pertussis cases, 422 outpatient cases, 146 hospitalizations and 0.54 deaths per year at the population level. With a 5% discount rate, 138.5 quality-adjusted life-years (QALYs) would be gained at an extra cost of AUS 4.44 million and an incremental cost-effectiveness ratio of AUS 32, 065 per QALY gained. Sensitivity and scenario analyses demonstrated that outcomes were most sensitive to assumptions around vaccine effectiveness, duration of protection in mothers, and disutility of unreported cases. In conclusion, dTpa vaccination in the third trimester of pregnancy is likely to be cost-effective from a healthcare payer perspective in Australia.